Bulgarian and Russian congruent idioms as indices of culturally specific conceptualizations - Lavrova, Nataliya A. (Вестник Томского государственного университета. Филология)
By virtue of common ancestry, Russian and Bulgarian have a lot of shared linguistic and cultural grounding. However, unique cultural conditions have given rise to set expressions that embed unique, culturally specific conceptualizations and cognition. This implies that although many Russian-Bulgarian idioms are structurally and semantically isomorphic, most of them embed conceptual elements that are unique to Bulgarian and Russian linguacultures. Taking this tenet as the premise for our research, we see its main aim in demonstrating that despite structural and semantic parallels between Russian and Bulgarian set expressions, the majority are repositories of unique, culturally specific conceptualizations and thus reflect cultural cognition which is not the same across Russian and Bulgarian native speakers. The hypothesis of the research is that despite the semantic and structural congruence between Bulgarian-Russian idioms, the emergent cultural cognition has a bearing on the conceptual content conveyed by structurally and semantically isomorphic idioms. This difference reflects underlying conceptual differences in cultural cognition. The main methods of the research are (1) the conceptual-associative experiment, (2) random sampling, (3) linguistic experimentation, (3) the one-tailed T-test statistical analysis. From the Russian-Bulgarian Dictionary of Idioms (Russko-Bolgarskiy Frazeologicheskiy Slovar') by K. Andrejchina (edited by S. Vlahov), 100 idioms were selected through random sampling. These idioms were interpreted by 50 native speakers, who were matched on such parameters as age and socio-economic background: all are university graduates, with the mean age of 32 years. The statistical tool one-tailed T-test substantiated the working hypothesis and revealed that there is a statistically significant difference in culturally specific conceptualizations embedded in congruent Bulgarian-Russian idioms. Avenues for further research include the following aspects of investigating culturally specific conceptualizations connected with idiomatic language. Associations with idioms from two distantly related or unrelated languages could be compared in order to find out to what degree linguistic proximity has a bearing on the amount of comparable or divergent associations. Research could also be carried out in such a way that cross-generational differences between associations elicited from older and younger generation of speakers of two or more languages are compared and intergenerational inconsistencies are plotted on a diagram so that a picture of the relevant differences emerges.